Implementasi Hukum Penerapan Pidana Tambahan Bagi Penggedar Narkotika Golongan I (Studi Wilayah PN. Lubuk Pakam) - Kristin Devi Yanti (Universitas Medan Area, 2022)
This study aims first to find out the form of the relationship between Police Investigators and Public Prosecutors and Judges in law enforcement of narcotics illicit trafficking and to know the urgency of applying additional punishment for class I narcotics dealers in the perspective of sentencing theory. This type of research is empirical juridical. This type of research is used because the research is directly related to the community to be studied. This type of research was carried out by analyzing data and interviews, then analyzed qualitatively. The first result of the research is that the relationship between Police Investigators and Public Prosecutors and Judges is an integral part of the Indonesian criminal justice system. The second result, that the application of additional punishment for class I narcotics traffickers aims to provide legal certainty in the perspective of criminal theory as well as provide benefits to the state such as confiscation of the assets of the accused which will become state property and can be utilized by the state for the benefit of the wider community. In addition, the announcement of the judge's decision in the mass media, for example, will have a preventive effect on the public not to commit crimes of narcotics distribution. The third result, is an additional form of punishment that is in accordance with the Indonesian penal system that can be applied to class I drug dealers, namely the confiscation of certain goods and the announcement of a judge's decision as a form of additional criminal application